A light–heat synergism in the sub-bandgap photocatalytic response of pristine TiO2: a study of in situ diffusion reflectance and conductance. Issue 9 (17th February 2022) - Wu, Zhizhou; Li, Liuyang; Zhou, Xuedong; Parkin, Ivan P.; Zhao, Xiujian; Liu, Baoshun
Abstract : The sub-bandgap light-heat synergism induced electronic transition and their role in photocatalysis were revealed by means of in situ diffusion reflectances and (photo) conductances. Abstract : Pristine TiO2 materials are mainly used as photocatalysts under super-bandgap light illumination. The sub-bandgap (SBG) photocatalytic response has seldom been investigated and the mechanism of action remains unclear. In the current research, we firstly study the SBG light electronic transition of pristine P25 TiO2 by means of in situ diffusion reflectance and (photo)conductance measurements under finely controllable conditions. It is revealed that the SBG light can promote valence band (VB) electrons to the exponentially-distributed gap states of the TiO2, which can then be thermally activated to the CB states. A hole in the VB and an electron in the CB can be generated by the synergism of a SBG photon and heat. It is also seen that the photoinduced electrons can transfer to O2 through the CB states, and that the holes can be captured by isopropanol molecules. As a result, isopropanol dehydrogenation can occur over pristine TiO2 under SBG light illumination. It is seen that the photocatalytic activity increases with temperature and the energy of the SBG photons, in agreement with the light–heat synergistic electric transition via the exponential gap states. The present research reveals a mechanism for the SBG light photocatalytic response of pristine TiO2 materials, which is important in designing highly-active visible light active photocatalysts.